Intervention Size and Persistence - Kondylis, Florence (World Bank, Washington, DC, 2021)
Do larger interventions improve longer run outcomes more cost effectively? And should poverty traps motivate increasing intervention size? This paper considers two approaches to increasing intervention size in the context of temporary unconditional cash transfers — larger transfers (intensity), and adding complementary graduation program interventions (scope). It does so leveraging 38 experimental estimates of dynamic consumption impacts from 14 developing countries. First, increasing intensity decreases cost effectiveness and does not affect persistence of impacts. This result can be explained by poverty traps or decreasing marginal return on investment in a standard buffer stock model. Second, increasing scope increases impacts and persistence, but reduces cost effectiveness at commonly evaluated time horizons and increases heterogeneity. In summary, larger interventions need not have more persistent impacts, and when they do, this may come at the expense of cost effectiveness, and poverty traps are neither necessary nor sufficient for these results.